Standardisation of Tissue/ Meristem Culture Techniques in Important Horticultural Crops - Rajmohan K (Department of Plantation Crops and Spices, College of Horticulture, 1985)
Attempts were made in the Plant Tissue Culture Laboratory of the College of Horticulture, during 1981-85 to standardize tissue culture techniques for the propagation of some of the important horticultural crops of Kerala. Explants from shoot apices of fresh stem sprouts of five year old jack (Artocarpus heterophyllus Lam.) trees registered a multiplication rate of 4.5 x when cultured for five weeks and produced 70% rooting (in 13.43 days) with 5.43 roots per shoot. The MS medium supplemented with GA 1.0ppm and activated charcoal 1.0% was identified as suitable for culture establishment, supporting the survival and initial growth of the explants. Benzyl adenine 5.0ppm was found to be the optimum cytokinin level for the production of fairly elongated multiple shoots and NAA 0.2ppm was identified as the optimum auxin level for supporting the growth of the cultures. The normal strength of the inorganic salts and organic growth factors of the MS medium, with 3 – 4% sucrose or 2 – 3% glucose was found to support the multiplication and growth of jack shoot cultures. GA3 did not influence the shoot proliferation or growth. Adenine sulphate at 20ppm was found to increase the multiplication rate by 27.3%, without affecting the growth of the cultures. Adenine as well as casein hydrolysate were found to be not beneficial. The Anderson’s medium was found to be unsuitable to support the proliferation and growth of jack shoot cultures. Serial subculturing for 10 times at 4 week interval was found to increase the multiplication rate to 5.39x. The MS medium supplemented with BA 2.0ppm, NAA 0.2ppm and insoluble PVP 500ppm was found to be suitable for shoot elongation. Half strength of the MS inorganic salts, full strength of the MS organic factors, 3% sucrose and 0.6% agar were found to be the optimum for the in vitro rooting of jack shoot cultures. When planted out, the plantlets were observed to have 55.6% survival. Callus production was made possible from explants of shoot apices, internodal segments, leaf segments and root apices. Efforts to induce re-differentiation in the callus, direct organogenesis and direct/callus mediated somatic embryogenesis were not successful. Shoot apices from the seedlings registered a multiplication rate of 17.4x. In this case, the percentage of rooting was 100, with 6.0 roots formed in 20.75 days. Explants from fresh stem sprouts of ten year old and thirty year old trees recorded a shoot multiplication rate of 2.8 and 2.09, respectively in five weeks. In the former, the rooting percentage was 40 with 2.5 roots produced in 24 days, after 2-3 subcultures. In the latter, there was 15% rooting with 2.0 roots formed in 46.7 days, after 2-3 subcultures. Explants from six-month old jack grafts failed to produce multiple shoots and exhibited 50% rooting with 2.0 roots formed in 20.5 days. Cytological examination revealed the stability of chromosome number in the plantlets. Anatomical studies revealed the presence of thin culture in the leaves of the young plantlets. The procedure for the in vitro clonal propagation of jack through the enhanced release of axillary buds involved agitating the surface sterilised shoot apices in a solution of 0.7% insoluble PVP + 2% sucrose for 30-45 minutes and keeping them in sterile water at 4-50C for 24 hours followed by disinfection (3% sodium hypochlorite solution for 5 minutes and 0.1% mercuric chloride solution for 10 minutes) and culture in the establishment medium (MS + GA 1.0ppm + activated charcoal 1.0%) in darkness for four weeks with repeated subculturing. The cultures were then exposed to light for two weeks, after which the growing shoot apices were transferred to the proliferation medium (MS + BA 5.0ppm + NAA 0.2ppm + adenine sulphate 20ppm + insoluble PVP 500ppm). Shoots from the proliferation medium were transferred after five weeks to an elongation medium (MS + BA 2.0ppm + NAA 0.2ppm + insoluble PVP 500ppm). The shoots were then cultured on MS medium containing activated charcoal 1.0% for two weeks. For the in vitro root induction, the shoots were cultured in darkness in 1⁄2 MS + IBA 2.0ppm + NAA 2.0ppm + sucrose 3% + agar 0.6% (for 6 days) and then transferred to 1⁄2 MS without growth substances for root elongation. Just after the appearance of the roots, the plantlets were hardened by exposure to high light intensity (3500 lux) for one week. The plantlets were than transferred to vermiculture medium, under high relative humidity (90-100%) provided by microscope covers. The plants were watered with a solution of the MS inorganic salts at half strength. After another gradual hardening process and as new leaves were produced, the plantlets were transferred to garden pots and kept in the open field conditions. The cost of production of one jack plantlet, including one month’s hardening was worked out to Rs.9.09. Explants of mussaenda (Mussaenda ervthrophylla Schum. Thonn.) were effectively surface sterilized by treating with 0.1% mercuric chloride solution for 15 minutes. The suitable culture establishment medium was identified as MS + BA 0.5ppm + kinetin 0.5ppm. A shoot multiplication rate of 2.75x was realized in a period of four weeks on MS medium supplemented with BA 0.5ppm and kinetin 0.5ppm. Sub- culturing was found to increase the multiplication rate to 2.95x. Full strength of the MS inorganic salts was found to support the proliferation and growth of mussaenda shoot cultures. Adenine sulphate, auxins and Anderson’s medium were found to be not beneficial. The shoots were made to root on MS medium containing half strength of the inorganic salts and full strength of the organic growth factors, 3% sucrose, 0.6% agar, 0.4ppm IBA and 0.4ppm NAA, under dark conditions in 37 days. Anderson’s rooting medium was found to be inefficient for the in vitro rooting of mussaenda shoot cultures. Attempts for planting out were not successful, probably due to the low number of roots (which were weak and slender), the development of callus at the root-shoot junction and the partial withering and yellowing of the shoots by the time the roots were initiated. Attempts for the direct planting out of the shoots pretreated with IBA solution were not successful. Segments of ovary wall was identified as the best source of explant for callus production, registering a callus index value of 400, at the best treatment (NAA/kinetin combinations 2.0 + 1.0ppm and 4.0 + 2.0ppm). Shoot regeneration from the callus occurred at a frequency of 33.3% on MS medium supplemented with BA 2.0ppm or BA/kinetin combinations 0.5 + 0.5ppm and 0.5 + 0.3ppm. Root regeneration was observed at a frequency of 66.7% with 13.33 roots per culture on MS medium containing kinetin/NAA combination 2.0 + 8.0ppm after 60 days’ culture. Attempts for direct organogenesis were not successful. Globular structures resembling somatic embryoids having simultaneous root and shoot development were observed when the callus from the induction medium (MS + 2,4-D 2.0ppm + kinetin 1.0ppm) was transferred to MS medium containing BA/kinetin combinations 0.5 + 0.5ppm or 1.0 + 0.5ppm after 70 to 73 days culture. About 4.5 shoots with a tuft of miniature roots were formed per culture, at the best treatment. Attempts for inducing direct somatic embryogenesis were not successful. Preliminary studies on culture establishment were made for breadfruit (Artocarpus altilis L.) and nutmeg (Myristica Fragrans Houtt.). Slight callus production was made possible in both the cases. Preliminary studies on somatic organogenesis were made in the case of pepper (Piper nigrum L.). Callus production and redifferentiation were observed.